Detection of Salmonella Spp. in Pandalus borealis and Chlamys islandica by a Real Time qPCR Method and Partial Validation of qPCR in a Accredited Quality Control (QC) Laboratory of Bangladesh - Sarwer, Md. Golam; Nesa, Fayejun; Chowdhury, A. K. Jilani (Asian Journal of Biological and Life Sciences, 2017)
Salmonellosis is common worldwide and widespread in fisheries products of South Asia, especially Bangladesh because of poor post-harvest handling. For that, Salmonella is considered as one of the major causes of foodborne infection in public health which referred to as salmonellosis. More time and need many tests for the confirmation of pathogenicity is required by the conventional microbiological detection methods of Salmonella. Therefore, the requirement for more rapid and confirmatory methods of Salmonella detection becomes apparent. The purpose of this study was to apply the real-time qPCR (Quantitative Polymerase Chain Reaction) method for detection of Salmonella spp. in shrimp (Pandalus borealis) and scallop (Chlamys islandica), which is more convenient and less time consuming than conventional microbiological methods. PCR and real-time qPCR were initially tested and compared with pure culture of seven Salmonella spp. Each detection method was tested using artificially contaminated shrimp and scallop samples. The method validation of the real-time PCR method was performed according to ISO 17025 in contrast to qualitative, quantitative and reliability criteria of validation. The sensitivity of the real-time PCR, as well as the decreased time requirements of this detection method, would suggest its usefulness in commercial laboratory practices.
Keywords: Polymerase Chain Reaction (PCR); Real-time PCR; Salmonella spp.; Shrimp